Resistance Of Children's Households Against Parental Interference - Faqiyyuddin, Septiyan; Rahmadhani, Nining (Maqasid: Jurnal Studi Hukum Islam, 2024)
Family resilience from intervention by parents or in-laws. After marriage there are rights and obligations, and new recognition by other parties, but in reality forming a small family without all forms of parental interference cannot be done as a whole by some people. There is parental intervention in the child's household because it is based on a feeling of affection. In this research, it is a response effort to achieve family resilience to the problems of parental or in-law intervention in the home life of children or in-laws. This research is included in the type of library research using descriptive-analytic methods in obtaining and examining all the data obtained . The results of this research explain that parental intervention in children's households according to Islamic law is permitted on condition that if there is a breakdown in the child's household, in this case the parents act as hakam (peacemaker). Influencing factors are: living at home, lack of income for children or in-laws, and incompatibility between parents or in-laws and children or in-laws.